2007
DOI: 10.1016/j.physd.2007.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic behavior near planar transition fronts for the Cahn–Hilliard equation

Abstract: We consider the asymptotic behavior of perturbations of planar wave solutions arising in the CahnHilliard equation in space dimensions d ≥ 2. Such equations are well known to arise in the study of spinodal decomposition, a phenomenon in which rapid cooling of a homogeneously mixed binary alloy causes separation to occur, resolving the mixture into regions in which one component or the other is dominant, with these regions separated by steep transition layers. A critical feature of the Cahn-Hilliard equation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 46 publications
(108 reference statements)
1
17
0
Order By: Relevance
“…Theorem 1.2 verifies conditions (1) and (2) from p. 128 of [8]. In [8] it is shown that if these conditions hold then a nonlinear iteration can be closed on an appropriate integral equation for a perturbation function v(t, x) defined by…”
Section: Introductionmentioning
confidence: 62%
See 4 more Smart Citations
“…Theorem 1.2 verifies conditions (1) and (2) from p. 128 of [8]. In [8] it is shown that if these conditions hold then a nonlinear iteration can be closed on an appropriate integral equation for a perturbation function v(t, x) defined by…”
Section: Introductionmentioning
confidence: 62%
“…As observed in [8] (see also [17,18]), this Evans function is not analytic in a neighborhood of (λ, ξ ) = (0, 0). More precisely, the functions φ − 1 (x 1 ; λ, ξ ) and φ + 2 (x 1 ; λ, ξ ) fail to be analytic in this neighborhood.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations